Symptomatic thoracic spinal cord compression caused by postsurgical pseudomeningocele Compressão medular torácica sintomática causada por pseudomeningocele pós-operatória - Arthur de Azambuja Pereira Filho; Gustavo de David; Gustavo de Azambuja Pereira Filho; Albert Vincent Berthier Brasil (Arquivos de Neuro-Psiquiatria)
We report the first case of symptomatic thoracic spinal cord compression caused by postsurgical pseudomeningocele. A 49-year-old man sought treatment for progressive loss of strength in the lower extremities ten months after full neurological recovery for a thoracic (T11) intradural-extramedullary schwannoma. Magnetic resonance imaging revealed a postsurgical thoracic (T11-T12) pseudomeningocele. The surgical approach showed an inadequate dural closure with spontaneous cerebrospinal fluid fistula. The defect was sealed with suture, muscle and biological glue covering. The patient had a good recovery. Pseudomeningocele must take part of the differential diagnosis of myelopathy after thoracic spine surgery. Relatamos o primeiro caso de compressão medular torácica sintomática causada por pseudomeningocele pós-operatória. Paciente masculino, 49 anos, apresentou perda progressiva de força nas extremidades inferiores dez meses após recuperação neurológica completa de cirurgia para remoção de schwannoma intradural-extramedular torácico. A ressonância magnética dorsal revelou pseudomeningocele (T11-T12). A abordagem cirúrgica mostrou fechamento dural inadequado com fistula liquórica espontânea. O defeito foi corrigido com sutura, músculo e cola biológica. O paciente teve boa evolução pós-operatória. Pseudomeningocele deve fazer parte do diagnóstico diferencial de mielopatia surgida após cirurgia na coluna dorsal.